Who is suffering from the “corona blues?” an analysis of the impacts of the COVID-19 pandemic on depression and its implications for health policy - Kim, Sunhee; Kim, Seoyong (International Journal of Environmental Research and Public Health, 2021)
COVID-19 is tremendously affecting not only social structures but also people’s psychological states. In particular, COVID-19 is negatively affecting psychological health, in particular, the depression. When individuals are experiencing the depression, there is increase in the suicide rate and occurrence of serious social problems. This study therefore examines factors affecting depression by using hypothesis testing. Previous studies have limitations in that they focus only on demographic variables or other specific variables. In contrast, this study focuses on the influences of four non-pandemic and seven pandemic-related variables on people’s depression. We analyze data from a social survey (N = 1525) in Korea which adopted the stratified quota sampling method. Results show that, first, among the demographic variables, young people experience depression to a greater extent than older people do. Second, among the non-pandemic variables, individuals with more social support, good health, optimism, and self-efficacy exhibit lower levels of depression. Third, among the factors related to COVID-19, fear of infection, financial instability, personal lifestyle changes, and poor health status increase depression.
Keywords: Adolescent; Aged; Anxiety; COVID-19; Depression; Health Policy; Humans; Pandemics; SARS-CoV-2; Social Structure; Anxiety; Corona blues; COVID-19 pandemic; Depression; Health policy